Pengaruh Ekstrakurikuler Terhadap Prestasi Belajar Siswa Di Kelas IV MIN Sibuhuan - Era Mutiah; Irma Sari Daulay; Siti Maryam Nst (Journal Innovation In Education, 2023)
The Effect of Extracurriculars on Student Achievement in Class IV MIN Sibuhuan. This study aims to: find out how extracurricular activities are carried out at MIN Sibuhuan. Knowing how student achievement at MIN Sibuhuan. Mengetahui apakah ada pengaruh ekstrakurikuler terhadap prestasi belajar siswa di MIN Sibuhuan. Penelitian ini menggunakan pendekatan kuantitatif. Data collection techniques used are observation, documentation, and questionnaires. The sample in this study was 38 students, the total population consisted of 12 boys and 26 girls. Teknik analisis data menggunakan analisis deskriptif, inferensial product moment dan uji hipotesis. Based on the results of the study it was found that: (1) The extracurricular implementation at MIN Sibuhuan was very good in terms of the scores obtained by students, namely the highest score was 94 and the lowest was 78. Data analysis techniques using descriptive analysis, product moment inferential and hypothesis testing. (2) The learning achievement of students at MIN Sibuhuan who take part in extracurriculars is very good, judging by the test results obtained, namely the highest score is 90 and the lowest score is 63. (3) the research results prove that extracurricular activities have a positive influence on students. Because tcount > ttable (3.55 > 2.024) then Ho is rejected and Ha is accepted. This means that the hypothesis proposed is in accordance with the results of the study, namely that there is a significant influence between extracurricular activities on student achievement at MIN Sibuhuan.